(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Student fitness program Courtesy of the President’s Council on Physical Fitness Courtesy of the President’s Council on Physical Fitness An individual’s physical and mental well-being is the concern of two similar areas of education: health education and physical education. Both deal with habits of exercise, sleep, rest, and recreation. Since physical well-being is only one aspect of a person’s overall health, physical education is often thought of as a part of health education. Health education is an activity aimed at the improvement of health-related knowledge, attitudes, and behavior. It is used in schools to help students make intelligent decisions about health-related issues. There are many ways to teach health in schools. Usually instructors create and facilitate learning experiences that develop the student’s decision-making skills. Above all, teachers provide health information and a concern for factors that influence the quality of life. Health behavior plays a major part in a person’s overall well-being. Since health-related behaviors are both learned and amenable to change, formal health education usually begins when a child is most flexible—in primary school. This is also when a child is more apt to accept positive health behaviors. It is in these early years that the negative effects of a lifetime of health abuse can be prevented. Many health problems are known to be linked to smoking, poor nutrition, obesity, lack of exercise, stress, and abuse of drugs and alcohol Basic to health education is the principle of preventive care. Health educators attempt to teach people to be responsible for their own health and health care. They also discuss the benefits of medical technology and research. They often promote behavioral changes and modifications to improve health. Health education and physical education programs exist throughout the world. In the United States, most health education and physical education programs are managed by governments (federal, state, and local), communities, schools, and organizations.